Slope Mapping using Unmanned Aerial Vehicle (UAV) - Muhammad Farhan, Zolkepli; Norlinda, Mohd Rozar; Mohd Fakhrurrazi, Ishak; Mohamad Hazeem, Mohmad Sidik; Nurul Amira Syuhada, Ibrahim; Muhammad Syamsul Imran, Zaini (TURKBILMAT Education Services, 2021)
This paper discusses the applications of unmanned aerial vehicle (UAV) for slope mapping and also its important parameters including perimeter, area and also volume of certain selected area. With the development of modern technology, the utilization of UAV to gather data for slope mapping becoming easier as it is quick, reliable, precise, cost-effective and also easily to operate. Modern UAV able to take high quality image which essential for the effectiveness and nature of normal mapping output such as Digital Surface Model (DSM) and Digital Orthophoto. This photo captured by UAV will later transfer to commercial software to generate full map of study area. With the help of established software, the measurement of selected study areas can be determined easily which can be considered as the main interest in this study. In addition, another outcome of this study is, this modern method of mapping will be compare to traditional method of mapping which proven to be more effective in term of low costing, low time consuming, can gather huge amount of data within short period of time, low man power needed and almost no potential risk of hazardous effect to man.